Assessment of the expediency of cross-platform software development - Medvediev, V. S.; Liutenko, Iryna Victorivna (Одеська національна академія харчових технологій, 2020)
Recently, the mobile applications have emerged with the uprising smartphone trend. Now-a-days, ahuge number of mobile operating systems require more developments, in order to achieve that, Open source cross-platform mobile frameworks came up, in order to allow importing the same code on various operating systems. In this paper, the focus is made on commonly used mobile development methods, and a process that selects the most suitable solution for a particular need is proposed.
Keywords: software development; cross-platform software development; applications; services; business models; business strategies